The influence of leadership, training, competence on lecturer performance in higher education - Arniati Arniati; Muryani Arsal (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The research was conducted to determine the effect of leadership, training, competence on the performance of lecturers of the Development Economics Study Program, Faculty of Economics and Business, University of Muhammadiyah Makassar. This study uses a quantitative approach, the survey design provides questionnaires, interviews, and observations to a target sample of 46 people. The sampling technique used was purposive sampling. The data were then analyzed using descriptive analysis and the analytical method used was multiple linear regression analysis with the help of SPSS26 in hypothesis testing. The results of this study indicate that leadership has a positive and significant effect on the performance of lecturers in the Development Economics Study Program, Faculty of Economics and Business, University of Muhammadiyah Makassar. Training has a positive and significant effect on lecturer performance. Competence has a positive and significant effect on lecturer performance. Leadership, training, competency simultaneously have a positive and significant effect on lecturer performance.